Advancing Clinical Decision Support Systems for the Management of Neonatal Nutrition: Barriers to Implementation - Falciglia, Gustave H; Sierra-Fernandez, Hernan; Freeman, Melissa; Healy, Daniel; Wicks, Jennifer S; Robinson, Daniel T (Research and reports in neonatology, 2022)
Purpose: Few clinical decision support systems (CDSSs) are available to help clinicians calculate nutrition intake in infants in the neonatal intensive care unit (NICU) despite improvement in the accuracy of calculations and quality of nutrition delivered. The aim of this manuscript is to qualitatively define the barriers associated with the implementation of CDSSs to calculate fluid and nutrition intake. Methods: After defining the data necessary to calculate fluid and nutrition intake, multidisciplinary groups analyzed CDSS capabilities and barriers to implementation at two academically affiliated NICUs. They implemented CDSSs to calculate intake received in the past (retrospective) and to estimate future intake from orders (prospective). Barriers and measures to reduce them are reported. Results: Barriers to implementation include simultaneous enteral feeding orders, the use of free text in the electronic health record (EHR), and a large variety of enteral feeding types for clinical use. These barriers made implementation of prospective CDSSs more difficult. CDSSs reported values that were normalized by both the most recent measured weight (usually obtained daily) and a dosing weight, a weight updated less frequently and used by pharmacies to facilitate prescribing. Conclusion: Despite using an EHR from the same vendor, different solutions were implemented at each NICU. CDSSs improved access to individual infant data on fluid and nutrition intake; however, none of the CDSSs easily exported data to monitor the quality of intake for the entire NICU or specific populations (eg, infants with bronchopulmonary dysplasia). Comprehensive CDSSs that include prospective intake and monitor the quality of nutrition intake through standardized values will require continued investigation and resources.